The welfare of dogs in Sweden, assessed from official animal welfare control - Teplova, Tamara (2016)
Dogs have a high popularity among pet owners in Sweden. Dog daycare and boarding establishment care for dogs when owners are at work or travel. These professional establishments require a license to conduct commercial activities. Compliance with Swedish and EU legislation pertaining to the welfare of animals is routinely assessed by educated inspectors. Complete data from official animal welfare control of premises with dogs in Sweden (21 counties), from January 2012 to December 2014, was provided by the Swedish Board of Agriculture. The objectives of the study were to identify missing data on dog welfare from the animal welfare control database; to determine the occurrence of poor welfare in general, and between professional and non-professional premises that keep dogs; to investigate whether the welfare status of dog daycare/boarding can be determined using the animal welfare control database; and recommend improvements for assessment, especially for dog daycare/boarding in Sweden. A species specific animal welfare checklist was used to assess compliance with legislation pertaining to the welfare of dogs. There were 40 control points based on animal, resource, and management-based measures on the animal welfare checklist. There were only four animal-based control points assessing social contact, cleanliness and grooming of the animals, body condition, and claw condition. During the study period it was found that there were a total of 17,660 premises registered with the Swedish Board of Agriculture. Eleven percent of these premises were registered as a professional establishment. The total number of inspections from 2012 to 2014 was 9245. Reasons for inspection included normal routine inspections 600, because of a complaint by the general public, veterinarian or other 5893, due to follow-up of a previously identified deficiency 1707, or because of an application for a permit to conduct a commercial activity 1045. Findings from this study have demonstrated that the most frequent animal-based welfare issues were for inadequate claw condition (19% non-compliant), followed by body condition (15%). The highest percentage non-compliant resource or management-based CPs were design requirements for dog yards (45%), followed by requirements for protection from inclement weather (e.g. strong heat, precipitation, humidity, wind and cold) while outdoors (29%). Also shown to have greater than 10% non-compliance were requirements for the regularity and length of walks, the facility cleanliness, space dimensions, environment and species-specific enrichment; and access to clean drinking water. I was able to determine significant differences in welfare between professional and non-professional establishments; however data was lacking on the type of professional establishments, and therefore dog daycare and boarding facilities were not easily identifiable. Improvements to the official animal welfare control database are recommended. The animal-based measures and the methods used to record them should be standardised; monitoring protocols should be improved by including factors that may have positive and negative effects on the animal welfare; the dog welfare checklist should have more animal-based CPs; data collection should be standardised; checklists should be more adapted for daycare and boarding establishments, and to create one common gold standard for dog welfare control.